1995
DOI: 10.1007/bf00919590
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence of ?nerve entrapment syndromes? and subclinical peripheral neuropathy in progressive systemic sclerosis (scleroderma)

Abstract: We report the electrophysiological findings and the management of 5 subjects with progressive systemic sclerosis (PSS) and clinical evidence of nerve entrapment. Three had carpal tunnel syndrome (CTS), 1 bilateral CTS and right tarsal tunnel syndrome (TTS) and 1 Guyon's canal syndrome. Only 1 patient (with CTS) showed significant clinical improvement after surgical decompression; the other 4 demonstrated a slight recovery of conduction without lasting clinical relief after conventional treatment. To explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
1
15
0
3
Order By: Relevance
“…This diuse damage is presumably related to distal peripheral neuropathy which may be subclinical, due to microangiopathy also aecting the vasa nervorum [1,10,12,14,15]. Similar subclinical neuropathy has also been encountered by us in nerves of the lower limbs [15], but no alterations in distal conduction have been demonstrated in subjects with only localized sclerosis (morphea) [16]. Peripheral nervous system involvement could play a role in the pathogenesis of RP in SS patients by altering vasomotor tonus [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This diuse damage is presumably related to distal peripheral neuropathy which may be subclinical, due to microangiopathy also aecting the vasa nervorum [1,10,12,14,15]. Similar subclinical neuropathy has also been encountered by us in nerves of the lower limbs [15], but no alterations in distal conduction have been demonstrated in subjects with only localized sclerosis (morphea) [16]. Peripheral nervous system involvement could play a role in the pathogenesis of RP in SS patients by altering vasomotor tonus [5].…”
Section: Discussionmentioning
confidence: 99%
“…Of the subjects, 13 had limited, and 5 diuse scleroderma. The clinical details and electrophysiological study of 14 of these 18 cases have already been published [15].…”
Section: Introductionmentioning
confidence: 99%
“…Details of methods have been published elsewhere [6]. Skin temperature was kept between 32°C and 35°C.…”
Section: Methodsmentioning
confidence: 99%
“…In mononeuropathy, conduction study of the nerve and/or EMG of the respective muscles were performed and compared with lateral or contralateral muscles or nerves [ 17]. Analyses performed in cases of motomeuronal syndromes have been reported elsewhere [23].…”
Section: Methodsmentioning
confidence: 99%
“…Motor conduction velocity from elbow to wrist, distal motor latency (DML) and compound muscle action potential amplitude (CMAPa) were also measured in the ulnar and median nerves. The exams were performed as described by Cioni et al [15] and as reported in detail elsewhere [16,17].…”
Section: Methodsmentioning
confidence: 99%